Implementasi P5 melalui Kolaborasi Musik Angklung dan Tari Tor-tor di Kelas IV Sekolah Dasar - Ansya, Yusron Abda'u; Salsabilla, Tania (FONDATIA, 2024)
This study aims to analyze and implement the Pancasila Student Profile Improvement Project (P5) through traditional arts collaboration for 4th grade students of Muhammadiyah Elementary School 29 Sunggal. This study uses a qualitative method with a classroom action research (CAR) design by integrating the West Javanese angklung game and the North Sumatran Tor-Tor dance into learning. The location of the study was Muhammadiyah Elementary School 29 Sunggal, where the study was conducted on 4th grade students of the 2023/2024 academic year from January 2024 to June 2024. The subjects of this study were 25 4th grade students of Muhammadiyah Elementary School 29 Sunggal. The results of the study showed that the P5 project improved students' understanding of Pancasila values, especially mutual cooperation and tolerance through active involvement in collaborative activities and the positive impact on students' cultural understanding and character was very visible. The evaluation highlighted the importance of adding training sessions, improving technical guidance, and integrating cultural activities into the regular curriculum. In conclusion, this P5 project has improved students' skills and understanding of Indonesian culture and strengthened Pancasila values, which have the potential to be applied to other classes in the future.